Ifá Divination, Knowledge, Power, and Performance - Abiodun, Rowland; Olupona, Jacob K. (Jacob Kẹhinde), 1951- (Book collections on Project MUSE., 2016)
This landmark volume compiled by Jacob K. Olupona and Rowland O. Abiodun brings readers into the diverse world of If-̀its discourse, ways of thinking, and artistic expression as manifested throughout the Afro-Atlantic. Firmly rooting If ̀within African religious traditions, the essays consider If ̀and If ̀divination from the perspectives of philosophy, performance studies, and cultural studies. They also examine the sacred context, verbal art, and the interpretation of If ̀texts and philosophy. With essays from the most respected scholars in the field, the book makes a substantial contribution toward understanding If ̀and its role in contemporary Yoruba and diaspora cultures.